2020
DOI: 10.3390/toxins12060405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Mycotoxin Modifiers and Mycotoxin Binders by Using an In Vitro Rumen Model as a First Screening Tool

Abstract: Ruminal microbiota of cattle are not able to detoxify all mycotoxins. In addition, detoxification can be hampered by adverse ruminal conditions (e.g., low ruminal pH). Hence, in the cattle husbandry, mycotoxin binders and modifiers could be used to prevent animal exposure to mycotoxins. In this study, an in vitro rumen model, including feed matrix, was established as first screening tool to test the efficacy of five products claiming to detoxify mycotoxins. The detoxifiers had different modes of action: (a) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
9
0
4
Order By: Relevance
“…In particular, with regard to ENN B, three binding products were tested (Binder 1: clay minerals and yeast derivatives; Binder 2: bentonite, leonardite, plant extracts, epoxidase; Binder 3: bentonite and sepiolite). The results demonstrated that all the binders partly adsorbed ENN B; however, while Binder 1 stably adsorbed the mycotoxin by 24% during all the incubation period, Binders 2 (28%) and 3 (22%) showed a reversible bond (desorption) since the differences between the ENN B concentration in the control and treated groups decreased over time [160]. Nevertheless, in vitro rumen models (Table 7) proved to be a suitable and flexible tool to investigate mycotoxin bioavailability in these species.…”
Section: In Vitro Rumen Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, with regard to ENN B, three binding products were tested (Binder 1: clay minerals and yeast derivatives; Binder 2: bentonite, leonardite, plant extracts, epoxidase; Binder 3: bentonite and sepiolite). The results demonstrated that all the binders partly adsorbed ENN B; however, while Binder 1 stably adsorbed the mycotoxin by 24% during all the incubation period, Binders 2 (28%) and 3 (22%) showed a reversible bond (desorption) since the differences between the ENN B concentration in the control and treated groups decreased over time [160]. Nevertheless, in vitro rumen models (Table 7) proved to be a suitable and flexible tool to investigate mycotoxin bioavailability in these species.…”
Section: In Vitro Rumen Modelsmentioning
confidence: 93%
“…As a consequence, mycotoxin control gains new importance in these species for the benefit of ruminant health and production. An in vitro rumen model was also applied to screen the efficacy of different commercial mycotoxin detoxifier agents [160]. In particular, with regard to ENN B, three binding products were tested (Binder 1: clay minerals and yeast derivatives; Binder 2: bentonite, leonardite, plant extracts, epoxidase; Binder 3: bentonite and sepiolite).…”
Section: In Vitro Rumen Modelsmentioning
confidence: 99%
“…Both for animal welfare and for economic reasons, it is advisable to carefully assess the activity of an enzyme intended to be applied as a feed additive under simulated digestive conditions in vitro prior to testing its efficacy in a feeding trial. In a previous publication, ZenA was shown to remove ZEN and prevent the formation of α-ZEL in an in vitro rumen simulation experiment [ 23 ]. However, degradation products of ZEN were not analyzed in this previous study.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced bioaccessibility in vitro or a reduced AFM1 excretion in cows exposed to feed with AF contamination above the legal limit can only provide supportive evidence (10). Surely, since the efficacy, and hence the health benefit, of mycotoxin binders must be assessed case-by-case, in vitro screening methods are of use, such as adsorption assays simulating physiological pH values (40)(41)(42)(43) or more complex models mimicking the rumen environment (44). From the -often overlooked -standpoint of safety, it is important to screen the interaction between mycotoxin binders and veterinary drugs with respect to the potential non-specific binding of drugs (45).…”
Section: Rbamentioning
confidence: 99%